Viral particle imaging by super-resolution fluorescence microscopy - Stefania Castelletto (Chemical Physics Impact, 2021)
Fluorescence microscopy provides a facile imaging methodology and potentials for imaging viruses in vivo. However, it is limited by the diffraction limit of light microscopy which is above the size of the virus particles. Fluorescence super-resolution (FSR) microscopy circumvents the diffraction limit. These techniques, an extension of fluorescence microscopy and alternative to electron microscopy, established over the past twenty years, have permitted the visualization of some virus components. Here, we summarize the principles of different FSR techniques and single virus tracking, and their current applications to virology studies, focusing on some limitations impeding their widespread use in virus replication and infection mechanism studies in living cells. In the specific context of virology studies and live-cell imaging, the advantages and disadvantages of the most known FSR methods are outlined with a focus on their current limitations such as labeling, imaging speed, photo-bleaching, depth of imaging, and the current attempts to overcome them. Some of the recent demonstrations encompassing the combination of different super-resolution (SR) approaches have provided answers to open questions as an example in the human immunodeficiency virus replication and from these experiences, further progress can be envisaged to reveal other viruses.